Pengaruh Kualitas Sistem, Kualitas Informasi, Penggunaan Sistem, Dan Kepuasan Pengguna Terhadap Dampak Individual (Studi Empiris Pada Bank Umum Di Jakarta) - Agustin Ekadjaja, Ricche Khosasi, (Jurnal Ekonomi, 2016)
The implementation of operational system is a necessity for the bank. However, the successful implementation of the system to the end-user of the systems have some little problems related to the end-user performance. The purpose of this research is to analyze and demonstrate empirically the effect of system quality, information quality, system use, and user satisfaction of the individual impact. The sample used by 75 respondents who were in the commercial bank in Jakarta. To answer the research hypothesis with IBM SPSS Statistic (Statistical Package for the Social Sciences) 21.0 software, multiple regression analysis is used in this test, after testing the assumption of classical test first. Based on the research results, it can be concluded that the system quality, information quality, system use, and user satisfaction have an effect to the individual impact. To get a better results, further research is recommended to add other variables to measure the effect of individual impact directly.